1990
DOI: 10.1002/art.1780330605
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and cartilage metabolism in rheumatoid arthritis. Studies of the Blood Markers Hyaluronic Acid, Orosomucoid, and Keratan Sulfate

Abstract: Single analyses of peripheral blood of rheumatoid arthritis (RA) patients showed a significant reduction in the mean value for keratan sulfate (KS) compared with that in control subjects, but the mean value for orosomucoid (OM) was elevated compared with that in control subjects. Some RA patients displayed highly elevated levels of hyaluronic acid (HA), while others exhibited normal levels. There was a significant inverse correlation between OM and KS content in RA patients, as well as a direct correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 29 publications
4
40
1
2
Order By: Relevance
“…Our study suggests that serum HA values are affected by the presence of involved OA joints in multiple sites in individuals without other serum-HA-related factors. This biomarker increases in the presence of articular synovitis and cartilage damage [6,7]. Inflamed synovium produces more HA locally and secretes it into the synovial fluid [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study suggests that serum HA values are affected by the presence of involved OA joints in multiple sites in individuals without other serum-HA-related factors. This biomarker increases in the presence of articular synovitis and cartilage damage [6,7]. Inflamed synovium produces more HA locally and secretes it into the synovial fluid [20].…”
Section: Discussionmentioning
confidence: 99%
“…There are many biomarkers for cartilage, bone and synovitis [5]. Among them, serum hyaluronan (HA) level is considered a good biomarker for reflecting cartilage damage and synovitis in OA patients [6,7]. Previous studies show its association with the presence [7][8][9], duration [10] and severity of radiographic OA [11]; degree of pain [5,11,12]; and OA progression [13].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that the levels of HA in the RA patients we studied were not as high as those in other RA patient groups (43) may reflect the fact that all of our patients had early disease, and thus had less inflamed synovial tissue mass than would be found in patients with more advanced RA. Elevated concentrations of HA in the serum of RA patients appear to be related to acceler- ated production of HA in inflamed joints, and the resultant increase in the amount of degradation products appearing in the serum (17)(18)(19)(20). Monokines, especially tumor necrosis factor CY and interleukin-1 a, which are detected in increased quantities in the joints of RA patients (21,22), stimulate HA production by synovial fibroblast-like cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to IA steroid injection, the albumin removal rate was significantly lower in OA than in RA patients (P = 0.005). Changes in albumin clearance were not significantly influenced by IA steroids in the AS patients, although there were decreases in the V, at 50-80 days post-IA steroid (P = 0.025), with the rates of albumin removal ranging from 2.01 to 6.00.…”
Section: Alterations In Clinical Variables As Presented Inmentioning
confidence: 78%
“…In contrast, the HA concentration in serum from RA patients is markedly increased (5-8). It has been suggested that these increases may be the result of synovitis (5,6,9) and associated alterations in the rate of HA clearance from RA joints. However, the relationship between the structural and physiological changes that occur during inflammation and the distribution of HA remain poorly understood.…”
mentioning
confidence: 99%